2020
DOI: 10.21203/rs.3.rs-72826/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Osteopontin as a Novel Biomarker for the Prognosis and Clinical Pathology of Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Evaluation of the feasibility for osteopontin (OPN) to serve as a biomarker in the prognosis and clinical pathological features of prostate cancer patients.Methods: The original publications related to osteopontin and prostate cancer were comprehensively searched in the online databases, including PubMed, Embase, Cochrane Library, Web of Science, Medline, Wanfang database and China National Knowledge Infrastructure up to August 2019. Results were analyzed by software Revman 5.3 and Stata 12.0. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In previous studies, increased OPN expression has been implicated in the malignant transformation of prostate epithelial cells, tumor progression [16] and patient survival [32]. In the present study, we reported higher OPN expression in samples from primary tumors with bone metastasis than in those lacking metastases, supporting the role of this protein in cancer cell progression, which is in agreement with human studies [16,35]. Our findings are similar to those reported by Kim et al [36] and Bramwell et al [15], who showed that human patients with metastatic cancer have higher circulating levels of OPN and tumors that are more likely to metastasize.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In previous studies, increased OPN expression has been implicated in the malignant transformation of prostate epithelial cells, tumor progression [16] and patient survival [32]. In the present study, we reported higher OPN expression in samples from primary tumors with bone metastasis than in those lacking metastases, supporting the role of this protein in cancer cell progression, which is in agreement with human studies [16,35]. Our findings are similar to those reported by Kim et al [36] and Bramwell et al [15], who showed that human patients with metastatic cancer have higher circulating levels of OPN and tumors that are more likely to metastasize.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Tan et al [38] demonstrated that high OPN expression in breast cancer cells promotes tumor growth and invasiveness. In PC, OPN plays a critical role in the development of castration-resistant diseases that are particularly challenging to treat [35]. However, more research is needed to fully understand the molecular mechanisms underlying the role of OPN in breast and PC and to develop effective OPN-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%